Altered beta-band functional connectivity may be related to 'performance slowing' in good outcome aneurysmal subarachnoid patients. (23rd April 2019) - Shah-Basak, Priyanka P.; Dunkley, Benjamin T.; Ye, Annette X.; Wong, Simeon; da Costa, Leodante; Pang, Elizabeth W.
Highlights: Neurological outcomes post aneurysmal subarachnoid hemorrhage (aSAH) have improved. However, patients still struggle with functional recovery and cognitive difficulty. MEG profiles during a working memory task show atypical connectivity in patients. Beta-band synchrony was reduced in patients and correlated with poorer performance. Mental slowness and memory deficits may be attributed to this beta-band impairment. Abstract: Recent evidence suggests that good neurological outcome in subarachnoid hemorrhage (SAH) does not equate to good neuropsychological and cognitive outcome. These individuals continue to face cognitive difficulties in tasks involving mental flexibility, short-term memory and attention, resulting in decreased independence in daily living and reduced ability to return to work. In the current study, we examined the functional connectivity profiles using magnetoencephalography (MEG) in SAH patients, versus controls, during a visual short-term memory, 1-back, task. Our results found that a global measure of MEG-based phase synchrony in the beta band (15–30 Hz), derived from a time window during correct recognition, significantly differentiated the controls from the patients. During correct recognition, the connectivity patterns in the controls were characterized by inter-hemispheric parieto-frontal connections, involving the posterior parietal cortex, while patients appeared to recruit an entirely different network of regions, involving the anterior frontal and temporal regions. Reduced beta-band synchrony during recognition was associated with overall poorer performance, demonstrated as lower accuracy and slower reaction times in patients, but not in controls. This differentiation between groups suggests an important and distinct role of beta-band phase synchronization, perhaps for memory retrieval, associated with good performance. Performance slowing, short-term memory and attention deficits in these patients may be attributed to the impaired beta-band connectivity among prefrontal regions and the posterior parietal cortex.